Chromosome aberrations induced in vitro by low doses of radiation: nondisjunction in lymphocytes of young adults. - Uchida, I A (1975)
Epidemiological studies suggest radiation exposure as a cause of meiotic non-disjunction in humans, but experimental evidence with cytological proof has been lacking. Our results indicate that mitotic nondisjunction of lymphocyte chromosomes can also be induced by exposure to a low dose of radiation. Abnormal segregation can be induced not only when the cells are irradiated but also when nonirradiated cells are incubated with irradiated cell-free plasma or serum. The X and no. 21 chromosomes appear particularly susceptible to nondisjunction.